2021
DOI: 10.1111/amet.13035
|View full text |Cite
|
Sign up to set email alerts
|

Contamination in theory and protest

Abstract: Contamination offers a new observatory for anthropological theory. But does it bring us closer to the world at hand? I have spent the past five years working with residents in Bennington, Vermont, and Hoosick Falls, New York, in pursuit of justice after the toxin PFOA was discovered in their drinking water. Turning from advocacy to writing, I've been struck by how prominent toxicity is becoming in certain currents of anthropological theory and how little those theories illuminate about the protests against con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Labelled ‘forever chemicals’ for their highly stable chemical structure and resistance to be broken down, PFAS are a group of over 9000 chemical compounds of escalating concern. Increasingly, research points to their toxicity, ubiquity and potential harms to human and environmental health (Bond, 2021; Fenton et al, 2021; Lenka et al, 2022; Renfrew & Pearson, 2021; Richter et al, 2021). Prior to any known consumer use, PFAS were first synthesised in the 1930s and used in the thermonuclear activity of the Manhattan Project in the 1940s (Gaines, 2023).…”
Section: Global Context and Theoretical Starting Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Labelled ‘forever chemicals’ for their highly stable chemical structure and resistance to be broken down, PFAS are a group of over 9000 chemical compounds of escalating concern. Increasingly, research points to their toxicity, ubiquity and potential harms to human and environmental health (Bond, 2021; Fenton et al, 2021; Lenka et al, 2022; Renfrew & Pearson, 2021; Richter et al, 2021). Prior to any known consumer use, PFAS were first synthesised in the 1930s and used in the thermonuclear activity of the Manhattan Project in the 1940s (Gaines, 2023).…”
Section: Global Context and Theoretical Starting Pointsmentioning
confidence: 99%
“…There is compounding evidence of PFAS' toxicity and research has been significantly focused on human health effects, recognising that ‘they [PFAS] have an affinity for living creatures’ (Bond, 2021, p. 388). For instance, an Organisation of Economic Cooperation and Development (OECD) hazard assessment concluded that PFOS (the most common of the PFAS family of compounds) was ‘persistent, bioaccumulative and toxic to mammalian species’ (OECD, 2002).…”
Section: Global Context and Theoretical Starting Pointsmentioning
confidence: 99%
“…It pinpoints the racialization of death and its nonrecognition in the “slow death” and dying that ecological devastation and contamination engender (Rodríguez Aguilera 2021). While the discipline of anthropology has taken a turn toward the Anthropocene, particularly in its theoretical conceptualizing of contamination and toxicity, this shift poses significant questions for retaining a grounding in the present material and embodied stakes of toxic geographies rather than a fixed orientation toward the theory's prospects for future possibilities (Bond 2021). As Bond cautions in the impetus toward positive articulations of the disruption and unsettling force of contamination,
How might ethnography hold together the shortcomings of the present and the alternatives that these wanting worlds gesture toward?
…”
Section: IIImentioning
confidence: 99%
“…Some scholars do. David Bond (2021, 393), for example, critiques the ceding of the political to the philosophical, asking how our research and writing might be generative for the people with whom we work, rather than only for social theory.…”
mentioning
confidence: 99%